The Monthly Labor Review at 100--part IV: employee benefits, industries and occupations, and worker safety and health since 1980. - Baker, Brian I. (Monthly Labor Review, 2016)
The article chronicles events in the areas of benefits, industries and occupations and workplace safety and health. It cites findings that although most private pension plans offered a lifetime minimum annuity of about 40% of a worker's accrued benefits to surviving spouses, spouses received a smaller share and many others were not covered at all. It notes the publication of articles on a range of industries that included ball and roller bearing, coal and health services.